2016
DOI: 10.1007/s10964-016-0483-5
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Growth Trajectories of Self-Esteem in Adolescence: Associations with Child Neglect and Drug Use and Abuse in Young Adulthood

Abstract: Neglectful rearing is linked with young adults' substance use and abuse, though the developmental mechanisms that underlie this association are unclear. The present study examines links between self-esteem growth during adolescence, childhood supervisory versus physical neglect severity, and substance use and abuse in young adulthood. A sample of youth was obtained from the Add Health study (N = 8738; 55.4 %-Female; 20 %-African American, 14.7 %-Hispanic). Growth mixture modeling analyses supported declining, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 61 publications
4
51
0
3
Order By: Relevance
“…Additionally, maladaptive psychosocial developmental outcomes, such as impaired self-regulation, delayed discounting, increased impulsivity, and low self-esteem, are associated with various health risk behaviors in adolescence, particularly substance use, risky sexual behavior, and physical inactivity (e.g., Farley and Kim-Spoon 2015; Kogan et al 2015;Oshri et al 2016) (not shown in Fig. 1).…”
Section: Health Impacts Of Psychosocial Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, maladaptive psychosocial developmental outcomes, such as impaired self-regulation, delayed discounting, increased impulsivity, and low self-esteem, are associated with various health risk behaviors in adolescence, particularly substance use, risky sexual behavior, and physical inactivity (e.g., Farley and Kim-Spoon 2015; Kogan et al 2015;Oshri et al 2016) (not shown in Fig. 1).…”
Section: Health Impacts Of Psychosocial Resourcesmentioning
confidence: 99%
“…In particular, lower-SES parents are more likely to lack necessary financial and material resources and parental knowledge, utilize a harsher, authoritarian, and rejecting parenting style, and engage in parental neglect and abuse. All of these adverse circumstances have been shown to impair the developmental trajectories of cognitive processing capacity and emotional regulation capacity as well as trajectories of educational attainment, mastery, selfesteem, and future orientation (e.g., Farley and Kim-Spoon 2015; Hampson et al 2007;Hardy 2006;Melby et al 2008;Nam and Huang 2009;Oshri et al 2016;Steinberg 2001;Zhang 2003).…”
mentioning
confidence: 99%
“…Self-esteem is high during early childhood, but then decreases when reaching adolescence. Upon reaching adulthood, one´s self-esteem increases and one experiences becoming more positive about oneself [25,32]. For this reason, we have chosen to study young adults, aged 16-24, as this represents a vital stage in their development of selfesteem, when they are most likely to harbour negative feelings about themselves, and most likely to require help in managing low self-esteem.…”
Section: Managing Self-esteemmentioning
confidence: 99%
“…If low self-esteem goes untreated, it can lead to development of conditions such as suicidal thoughts, eating disorders, substance abuse and depression [11,20,32,41]. Young adults, in particular, experience a decrease in personal self-esteem during the transition from childhood to adulthood [32]. While transitional changes are slow, young people can experience short-term fluctuations in their immediate feelings of self-worth [37].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, all of the articles selected from each journal issue are notable for their focus on relationships and their influence on development. They did so by focusing on emotional wellbeing (Oshri et al 2017;Schäfer et al 2017;Coelho et al 2017;Bluth et al 2017), economic adversity (Nieuwenhuis et al 2017; Ng-Knight and Schoon 2017), peer interactions (Shin 2017), sexual partners (Rossi et al 2017), justice system involvement (Wolff et al 2017) and schooling (Amemiya and Wang 2017;Geven et al 2017).…”
mentioning
confidence: 99%